Sign and Contained - Szkudlarek, Joanna (Hybris, 2020)
This paper is a reflection on the concept of sign presented by Ferdinand de Saussure in juxtaposition with the psychoanalytic notion of container/contained, presented by Wilfred R. Bion. The basic question of this paper concerns the types of relationships between signified and signifier and the container/contained. It is suggested that psychoanalytic work of Bion allows for supplementing de Saussure’s perspective with a spatial aspect of penetration of the signifier by the signified. Juxtaposing these two models creates a new conceptualization of sign, in which one of its elements enters the other, thus creating meaning. In this new conceptualization, two significant areas emerge, which are not direct parts of the sign, but are positioned in its immediate neighbourhood. They are given the names of the insignifier (insignifiant) and insignified (insignifié).